(untitled) (Voz e Cena, 2020)
This article describes a communications system for telematic performance developed during the COVID-19 pandemic of 2020. Taking the form of an antique telephone switchboard, the system is designed specifically for a solo performer to interact with voice recordings, music and sound synthesis mechanisms and engage with local and remote audiences via telephone.